2007
DOI: 10.1152/ajpheart.00575.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transport in rat vessel walls. II. Macromolecular leakage and focal spot size growth in rat arteries and veins

Abstract: Transendothelial lipid transport into and spread in the subendothelial intima of large arteries, and subsequent lipid accumulation, appear to start plaque formation. We experimentally examine transendothelial horseradish peroxidase (HRP) transport in vessels that are usually, e.g., pulmonary artery (PA), or almost always, e.g., inferior vena cava (IVC), atherosclerosis resistant vs. disease prone, e.g., aorta, vessels. In these vessels, HRP traverses the endothelium at isolated, focal spots, rather than unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…1 Since electron micrographs (45,46) show the PA and aorta have the same basic structural layers: endothelium, SI, IEL, media, and adventitia, Fig. 1, A and B, applies to both vessels the same basic 2-D convection-diffusion model (similar, but not identical, to that in Refs.…”
Section: Model Descriptionmentioning
confidence: 67%
See 4 more Smart Citations
“…1 Since electron micrographs (45,46) show the PA and aorta have the same basic structural layers: endothelium, SI, IEL, media, and adventitia, Fig. 1, A and B, applies to both vessels the same basic 2-D convection-diffusion model (similar, but not identical, to that in Refs.…”
Section: Model Descriptionmentioning
confidence: 67%
“…Chuang et al (9) and Shou et al (46) both observed this rapid HRP spot growth en face in rat aorta. HRP spots grow extremely rapidly in the first minute after HRP injection and more slowly thereafter.…”
Section: Growth Of Hrp Leakage Spotsmentioning
confidence: 87%
See 3 more Smart Citations